HUBUNGAN KARAKTERISTIK INDIVIDU, LAMA KERJA, DAN DUDUK TERHADAP KELUHAN LOW BACK PAIN PADA KARYAWAN PT ALTUS LOGISTICS SERVICES INDONESIA DI MASA PANDEMI COVID-19 - Khairana Anggraini, (2021)
Office workers are jobs with a high prevalence of musculoskeletal disorders (MSDs). MSDs in office workers usually occur on the back, hands, neck, arms, shoulders, and wrists. Low Back Pain is one part of MSDs, in the form of pain in the back area or the lower back, namely between the 12th rib and the buttocks fold which is factored by various things related to the individual and their work. The purpose of this study was to determine the relationship between individual characteristics, work hours and prolonged sitting on complaints of low back pain. This study used a cross sectional approach. The population of this study was employees of PT Altus Logistics Services Indonesia with a total sampling technique of 46 samples. The results of the analysis using the chi square test and fisher's exact showed the factors associated with low back pain complaints, gender (p-value = 0,013; POR = 11,88), work hours (p-value = 0,001; POR = 15, 19), and prolonged sitting (p-value = 0,009; POR = 19,43). Therefore, employees are advised to stretch every 20 minutes and maintain a healthy lifestyle.